You give me a name that I can't say, but I have to explain what it is every day: the power of poetry to share stories from young people with a rare disease. Issue 1 (2nd January 2020) - Livermore, P.; Wedderburn, L. R.; Gibson, F.
ABSTRACT: Qualitative research is about people's lives; their stories, their thoughts, their feelings, and their experiences. Researchers continue to reflect on the best way to present other people's stories in a way that stays true to their accounts and delivers the message in a manner which resonates. This article presents one such way, discovered through serendipity, which allowed the researcher to share findings from young people's stories eloquently and passionately to audiences of healthcare professionals from different disciplines. The silence and raw emotion witnessed after the poetry delivery was akin to that often seen during childbirth when those around are stunned into thoughtful awe. The poetry, which was crafted entirely from young participants' interview transcripts had two benefits; (1) sharing young people's stories using their own words and (2) using a presentation format that demanded attention; so that people took notice, listened and reflected on the words and experiences being expressed.